Exploring experiences of supports for suicide bereavement in Ireland: protocol for a national survey [version 1; peer review: 2 approved] - Selena O'Connell (F1000 Research Ltd, 2021)
Background A suicide death impacts upon the wellbeing of close family members and friends but has also been shown to affect many people outside of this immediate circle. This will be the first large-scale national study of adults bereaved or affected by suicide in Ireland, using a cross-sectional online survey. The overarching aim will be to gain insight into the experiences of supports received by people bereaved or affected by suicide and to identify the barriers to engagement following their loss. Methods A cross-sectional survey will be conducted among adults in Ireland who have been bereaved or affected by suicide. This project will seek to represent people with different demographics and backgrounds in the Irish population using a multifaceted approach to survey recruitment. A range of validated measures will be used to examine participants’ current wellbeing and grief experience. A combination of closed and open-ended questions will provide participants the opportunity to share their individual experiences, the services and supports available to them, and barriers and enablers to accessing supports. Results Quantitative data will be analysed using descriptive statistics. Chi-squared tests will be used to compare subgroups within categorical data items, and multivariable regression models will be used to examine differences in psychosocial and physical wellbeing across key groups. Qualitative content analysis will be used for qualitative responses to open-ended questions. Conclusions The survey will provide an in-depth understanding of the psychosocial and mental health impacts of suicide bereavement in Ireland; insight into the range of informal and formal supports accessed; and will identify unmet needs and challenges of accessing appropriate and timely supports. The findings will inform current national actions aimed at ensuring the standardisation and quality of the services and supports for those bereaved or affected by suicide.